Caveolae: A Role in Endothelial Inflammation and Mechanotransduction? - Shihata, Waled A.; Michell, Danielle L.; Andrews, Karen L.; Chin-Dusting, Jaye P. F. (Frontiers in Physiology, 2016)
Vascular inflammation and disease progression, such as atherosclerosis, are in part a consequence of haemodynamic forces generated by changes in blood flow. The haemodynamic forces, such as shear stress or stretch, interact with vascular endothelial cells, which transduce the mechanical stimuli into biochemical signals via mechanosensors, which can induce an upregulation in pathways involved in inflammatory signalling. However, it is unclear how these mechanosensors respond to shear stress and most significantly what cellular mechanisms are involved in sensing the haemodynamic stimuli. This review explores the transition from shear forces, stretch and pressure to endothelial inflammation and the process of mechanotransduction, specifically highlighting evidence to suggest that caveolae play a role as mechanosensors.